Optimizing the Ratio of Wind and Solar Power Stations - Kuznetsov N.; Smertiuk V.; Lysenko O.; Nesterchuk D.; Adamova S. (Problems of the Regional Energetics)
The purpose of the research is to determine criteria and calculate optimal ratio of different renewable energy sources (RES) for hybrid systems, estimate the random component of power fluctuation and consider the opportunities for its minimization. As a subject of the study it is variable and poorly forecasted in a short-term prospect character of generated power can negatively affect modes of grid operation. This concerns stability of dynamic processes in the systems of power supply. To develop a mathematical model of these processes a number of factual data on the climatic parameters and energy consumption regimes during the joint operation of solar and wind stations was used. As an experimental study suggests, the initial data were collected and statistically processed. Based on the results, mathematical models were developed in the form of a composition of deterministic and stochastic components and theoretical studies on the search for optimal ratios of capacities of wind and solar power stations were carried out. The object of optimization in the work is the load variability. As a combined single criterion, it was proposed to use the coefficient of variation. The ratios of the wind and solar components of the power generation, considered in this study, has allowed us to determine variants with a minimal dispersion of RES generation or with a minimum ratio of dispersion to average generated power which depends on the average annual or seasonal weather conditions. As a rule, the share of wind power plants should be 10-40% of the total rated RES power, depending on the total share of RES.